Biotechnology GATE 2019 - Agarwal (Arihant Publications, 2019)
Graduate Aptitude Test in Engineering examines the students' comprehensive understanding of various subjects from graduation for admission to various post graduate education programmes in elite institutes like II Sc IITs NITs and others. Gate Tutor series of books has been developed to serve as Unit wise and Topic wise study-practice guide for aspirants. 2019 edition of Biotechnology GATE Tutor has been developed to match the Question pattern of GATE exam. The book covers complete study material for General Aptitude and Engineering Mathematics with self-sustaining illustrations and variety of questions and their detailed answers. Each of the 3 units has an Intro Exercise and is divided into number of chapters further subdivided into smaller units for easy grasping. Previous Years' Solved Papers will help students to analyse the exam pattern and Online Mock Tests will put you into the real practice for improved performance.